The Vifaniia Monastery of Metropolitian Platon as Reflected in Russian Romanticism - Bashkirova, Mariya A. (Actual Problems of Theory and History of Art, 2022)
The Bethany (Vifaniia) Monastery was founded by Metropolitian Platon as his own residence and future shrine in 1783. During his lifetime the monastery became an important spiritual and intellectual center: Ivan V. Lopuhin, Ivan M. Dolgorukov, Ivan P. Turgenev, Fyodor B. Lubyanovskiy, and Emperor Pavel I were among the visitors, the Bethany Monastery was mentioned in Elisaveta P. Yan’kova’s memories as well as in the M. Wilmot’s and F. de Miranda’s writings. Shortly after the Platon’s passing, his monastery fell into disuse despite the imperial family patronage. The extensive repairs performed by Metropolitian Filaret (Droszdov) in the 1820 1830s have resulted in serious harm. However, in the same time, there was growing interest in the Vifaniia Monastery and the personality of Metropolitian Platon. In the writings by the Russian authors of the Romantic Age Andrew N. Murav’ev, Stepan P. Shevyrev, and Pavel P. Svin’in, the Vifaniia obtained “the second life”. The destruction of the monastery, coming soon after its suppression in the 1920th, didn’t allow the next wave of interest in the Vifaniia (particularly from researches of the 18th-century Russian architecture) to develop further. This article focuses on the perception of this unique orthodox monastery of the Age of Enlightenment in the travel narratives by the Russian romantic writers.
Keywords: The Bethany Monastery; Vifaniia; Metropolitian Platon Levshin; Metropolitian Filaret Drozdov; Andrew N. Murav’ev; Pavel P. Svin’in; Stepan P. Shevyrev; topography of Holy Land; Moscow architecture; last third of 18th century; travelogue; ekphrasis